THE USAGE OF ONOMATOPOEIA SOUND SYMBOL ON BOOK “DIARY OF A WIMPY KID” - Alfia Tawaffani Muslima (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The aim of the research is to know the ussage several of phonetic sign on a language, like onomatopoeia, phonesthemes and ideopone on the book "Diary of Wimpy Kids". The investigation is focused on the form and mean of a sound  symbol on the book called onomatopoeia. This research will be the background of a sound symbol sign as a description and the  writer presentation about what happen in that book for all of the reader . And the aim of the writing is to make the writer know more about the sound symbol of onomatopoeia on the story line of the book. The writer use the qualitative method on the research, the writer investigate, research , review and descript. The writer hope will get more about quality and the speciality of the onomatopoeia sound symbol. And the object of the research is the book of  "Diary of a Wimpy Kids", a book which popular among the young and adults's reader. The results of the research are the summary, review and meaningfull sentences which will be arranged by the writer so in the finally, the writer will know the deep information about type , meaning and the speciality of the onomatopoeia as the presentation/ description of the even and story line of the book specifically.